Sustainability Strategy and Development of Village Breeding Center: Evaluation of Morphometric Characteristics of Female Peranakan Ongole Cattle in Napis Village - Ali, Muhammad Irvan; Atmaja, Baluh Medyabrata; Hidayatulloh, Rifqi; Herviyanto, Doni; Kuswati (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2024)
This study evaluates the morphometric characteristics of female Peranakan Ongole (PO) cattle in Napis Village, Bojonegoro Regency, East Java, as part of a strategy for developing sustainable village breeding centers. The selection of the research location was conducted through purposive sampling, and the material in this study consists of female Peranakan Ongole cattle with age criteria (PI) based on the SNI for Peranakan Ongole cattle, namely PI0 (aged <1 year), PI2 (1 – 1.5 years), PI4 (1.5 - 2 years), PI6 (2 – 3 years), PI8 (aged > 3.5 years). Measurements include body height, body length, hip height, chest depth, chest circumference, ossa cervical vertebrae, ossa thoracic vertebrae, ossa vertebrae lumbar, ossa scapula, hip width, head length, head width and body weight, as well as morphometric indices such as head index, height slope, body index, index of compression, conformation index, length index, body ratio, proportionality and thoracic development on 206 female cattle grouped by age (PI0-PI8). Data were analyzed using multivariate analysis of variance (MANOVA) and post hoc tests, as well as key indices to identify growth patterns and body size stability. The research results show a significant increase in body size in the young-to-adult age group, where adult cows reach size stability. The morphometric index reveals consistent proportional development in the body of cattle as they age, reflecting structural maturity. Evaluation based on the Indonesian National Standard (SNI) shows that most cattle are in Class II and III, indicating excellent body quality in the productive age group. This research emphasizes that morphometric characteristics are important indicators in determining optimal management strategies to support the sustainability of local PO cattle development. These findings provide a foundation for the maintenance and development programs of the PO cattle population by prioritizing quality livestock management, supporting the conservation of local genetic resources, and enhancing cattle productivity in Indonesia.